2010
DOI: 10.2754/avb201079020307
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Radioulnar Incongruity of Elbow Joints and the Type of Fragmented Processus Coronoideus Medialis

Abstract: The aim of the study was to find the difference between actual and anticipated frequencies of individual types of FCP (fragmented coronoid process) in relation to the extent of radioulnar incongruity.We evaluated the radiographs of elbow joints (n = 135) of dogs (n = 77) with arthroscopically (n = 109) or arthrotomically (n = 26) proven fragmented coronoideus medialis ulnae. Radioulnar incongruity was classified as a congruent joint (0-0.5 mm), moderate incongruity (0.6-2 mm) and marked incongruity (> 2.1 mm).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Radio-ulnar incongruity has been the predominant focus of arthroscopic investigation of incongruity within the elbow joint due to its association with medial coronoid disease (1,5,16,17). The shift in radio-ulnar congruence seen in this study is small, with a mean change in radio-ulnar congruence of no more than 0.84 mm in any plane, which, in isolation, could be considered within the bounds of normal anatomic variation (11,21,22). In one study, mean radio-ulnar step in normal dogs in the sagittal plane was reported to be 0.21 ± 0.34 mm, with a range of 0 to 0.8 mm (11).…”
Section: Discussionmentioning
confidence: 66%
“…Radio-ulnar incongruity has been the predominant focus of arthroscopic investigation of incongruity within the elbow joint due to its association with medial coronoid disease (1,5,16,17). The shift in radio-ulnar congruence seen in this study is small, with a mean change in radio-ulnar congruence of no more than 0.84 mm in any plane, which, in isolation, could be considered within the bounds of normal anatomic variation (11,21,22). In one study, mean radio-ulnar step in normal dogs in the sagittal plane was reported to be 0.21 ± 0.34 mm, with a range of 0 to 0.8 mm (11).…”
Section: Discussionmentioning
confidence: 66%
“…It should be emphasized that the most frequently diagnosed lesion in medial coronoid process disease is a rupture of the medial coronoid process with complete fragmentation, which may occur even in the first few months of a dog's life. The separated fragments of the medial coronoid process may remain in place or be displaced within the joint cavity (10,33,37,50,41). According to some authors, apart from fragmentation, the frequently diagnosed abnormalities of the medial coronoid process include the presence of a fissure (visible in the CT image in the form of a hypoattenuating line) and chondromalacia (8).…”
mentioning
confidence: 99%